Highly oxygenated sesquiterpenes in Artemisia alba Turra. (February 2015) - Todorova, Milka; Trendafilova, Antoaneta; Danova, Kalina; Simmons, Luke; Wolfram, Evelyn; Meier, Beat; Riedl, Rainer; Evstatieva, Luba
Graphical abstract: Ten new sesquiterpene alcohols with germacrane, eudesmane, guaiane and oplopane skeleton were isolated from Artemisia alba Turra. Their structures were elucidated by spectral methods. Highlights: Ten new sesquiterpenoids were isolated from Artemisia alba . Highly oxygenated germacrane, eudesmane, guaiane and oplopane compounds were identified. Structures were established by spectroscopic methods, including NMR and MS analyses. Abstract: Ten new sesquiterpene alcohols of which seven germacranes, a eudesmane, a guaiane and an oplopane were isolated from the aerial parts of Artemisia alba Turra. Their structures and relative stereochemistry were elucidated by spectral methods ( 1 H and 13 C NMR, COSY, HSQC, HMBC, NOESY, and MS). In addition, the known 7-hydroxycadin-4-en-3-one, centaureidin and axillarin were found for the first time in the studied species.